From Books and Information to Excellence: Perspectives of Exploring and Modelling the Quality of School Libraries in Slovenia and Croatia - Vilar, Polona; Stričević, Ivanka (Monografija u povodu 20 godina rada Odjela za informacijske znanosti u Zadru, 2025)
The paper deals with the quality of school libraries in two neighbouring countries: Slovenia and Croatia. In both countries, school libraries had, until 1991, developed according to the same laws and standards which regulated the educational system and librarianship field. Since then, the development has been partly different but has still been based on the same theoretical findings, thus following the same fundamental professional guidelines. The paper starts with general views on researching school libraries, quality of school libraries, and then focuses on the situation in both countries. Emphasis is on the developments in research and theory between 2014 and 2024, which can be shown in the areas of researching and modelling competencies of school librarians and the quality of school libraries (including the resulting models), as well as investigating the role of school library in the curriculum, both in the context of developing information and other literacies and collaborating with the teachers. The differences in these areas between the two countries are presented and discussed to show the results and their implications for practice as well as to show how achievements in one country can benefit the other.